Life Expectancy and Entropy Values for Workers of Pachycondyla striata (Hymenoptera: Formicidae: Ponerinae) - da Silva-Melo, Adolfo [UNESP]; Giannotti, Edilberto [UNESP] (California State University, 2011)
We investigated the life expectancy and entropy value for workers of the ant Pachycondyla striata. Seven nests were excavated and these colonies were raised in laboratory conditions. The workers have a mean life-span of 74.48 days, these have a high mortality rate in the period of 1 to 85 days with a high entropy value of H = 0.611, confirming the number of deaths in the initial period.
Keywords: worker longevity; mortality rate; life table; Pachycondyla striata; Ponerinae